Effect of energy on the formation of flexible hard Al-Si-N films prepared by magnetron sputtering. (November 2016) - Musil, J.; Javdošňák, D.; Čerstvý, R.; Haviar, S.; Remnev, G.; Uglov, V.
Highlights: Flexible Al-Si-N films can be prepared by magnetron sputtering. Flexibility of the film is controlled by the energy delivered to the growing film. The energy is controlled by ion bombardment.